Beware of Cybercrime in Tax Reporting: Threats and How to Protect Yourself - Syahril, Muh. Akbar Fhad; Karović, Sadmir (Fakultas Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2025)
Information and communication technology development has brought significant changes to the taxation system, including the emergence of increasingly complex cybercrimes. This study aims to analyze the evolution of cybercrimes in the digital taxation system and the strategies and challenges in dealing with them. The method used is qualitative normative with a literature study approach. The study results indicate that cybercrimes in taxation include identity fraud, fake tax refund schemes, and international tax evasion, with significant financial impacts. Law Number 1 of 2024 concerning the Second Amendment to the UU ITE provides a more substantial legal basis but still requires harmonization with existing tax regulations. The handling strategy involves applying digital forensics, artificial intelligence, and international cooperation. The main challenge lies in the complexity of cybercrime, which continues to grow, and the need for more comprehensive regulations. This study concludes that a holistic approach is needed to strengthen rules, increase technological capabilities, and educate taxpayers to overcome taxation cybercrimes in the digital era.